Educational Robotics Workshop for Developing Wasaka Character - Dewantara, Dewi; Hartini, Sri; Cahyono, Gunawan Rudi; Hutabarat, Putri Pradita; Arifin, M Ilham; Az-Zahra, Siti Fathimah; Nurahma, Yosnandia Dwi (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
The community service activity was carried out as an effort to enhance the competence of physics teachers in Hulu Sungai Selatan Regency in designing contextual, innovative, and culturally rooted learning. The partner of this activity was the MGMP (Musyawarah Guru Mata Pelajaran) of physics, consisting of 22 teachers. This activity adopted the Participatory Action Research (PAR) method, involving teachers as active participants throughout the process.  The program was conducted through several stages, namely socialization, training, robotics practice, mentoring, and evaluation. This approach ensured that the solutions developed were relevant and aligned with the needs and capacities of the teachers. The medium used was ArtecRobo, which supports the application of technology-based learning. The results of the activity indicated an improvement in teachers’ understanding of integrating the Wasaka character—reflecting resilience and consistency—into physics learning through authentic experiences of assembling and programming robots. Teachers not only gained technical skills but also directly experienced how robotics can foster perseverance, collaboration, and problem-solving abilities. Participant responses were positive, with 87% of teachers stating the activity was highly beneficial and 80% reporting that they were motivated to implement it in their classrooms. The implication of this activity is the need for continuous mentoring and the provision of robotics facilities in schools so that the integration of Wasaka character can be optimized and support the achievement of 21st-century skills.